Membongkar penyelewengan mencari kebenaran : karya pemenang Anugerah Kajai, hadiah kewartawanan Malaysia MPI Petronas, 1982-2012 - Chamil Wariya Dato' (Malaysian Press Institute, 2012)
News writing on various issues happening in Malaysia; prize winning articles of the Kajai Award from 1980 to 2011, the highest accolade for journalists in Malaysia.